PHYSICOCHEMICAL AND ANTIOXIDANT PROPERTIES OF DIFFERENT MILLING FRACTIONS OF INDIAN WHEAT CULTIVARS - SNEH PUNIA; KAWALJIT SINGH SANDHU (International Journal of Pharma and Bio Sciences, 2016)
Wheat cultivars were studied for their physical properties (1000 kernel weight, bulk density, and l/b ratio). They were debranned and milling fractions obtained were bran and refined wheat flour (RWF). Whole wheat flour (WWF) was also obtained by milling the grains without removal of bran portion. These fractions were studied for their hunter color characteristics and antioxidant (total phenolic content, TPC; antioxidant activity, AOA; and total flavonoids content, TFC properties. Total phenolic content, total flavonoids content, and antioxidant activity differed significantly (p<0.05) among cultivars for different fractions. Studies revealed that bran fraction had significantly (p<0.05) higher bioactive compounds than other fractions for the cultivars studied. TPC, TFC and AOA followed the order: RWF<WWF<bran. Thus wheat bran, may serve as an excellent source of raw material for its potential applications as nutraceuticals and functional food ingredients.